1997
DOI: 10.1021/om9702791
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and IR/UV−Vis Spectroelectrochemical Studies of fac-[Mn(X)(CO)3(iPr-DAB)]n (n = 0, X = Br, Me, Bz; n = +1, X = THF, MeCN, nPrCN, P(OMe)3; iPr-DAB = 1,4-Diisopropyl-1,4-diaza-1,3-butadiene) at Variable Temperatures:  Relation between Electrochemical and Photochemical Generation of [Mn(CO)3(α-diimine)]-

Abstract: Electrochemical and IR/UV-Vis Spectroelectrochemical Studies of fax-[MnX)(CO)3(iPr-DABGeneral rights It is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
52
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 41 publications
(86 reference statements)
10
52
0
Order By: Relevance
“…This intriguing reduction pathway appears to be a characteristic property of the complexes [Mn(R-diimine)(CO) 3 -(halide)] with basic R-diimine ligands, as it was also observed for the related compound [Mn(iPr-DAB)-(CO) 3 Br] (iPr-DAB ) N,N′-diisopropyl-1,4-diaza-1,3-butadiene). 32 On the other hand, the reason for the absence of the 2e catalytic route in the case of [Mn(bpy)(CO) 3 Cl] seems to be different. Recent studies of bonding properties of the anions [M(iPr-DAB)(CO) 3 ] -(M ) Mn, Re), 32,33 which can also be extended for [M(bpy)(CO) 3 ] -(M ) Mn, Re), have revealed that the electron density on the fivecoordinate metal center significantly increases in the order Re < Mn, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…This intriguing reduction pathway appears to be a characteristic property of the complexes [Mn(R-diimine)(CO) 3 -(halide)] with basic R-diimine ligands, as it was also observed for the related compound [Mn(iPr-DAB)-(CO) 3 Br] (iPr-DAB ) N,N′-diisopropyl-1,4-diaza-1,3-butadiene). 32 On the other hand, the reason for the absence of the 2e catalytic route in the case of [Mn(bpy)(CO) 3 Cl] seems to be different. Recent studies of bonding properties of the anions [M(iPr-DAB)(CO) 3 ] -(M ) Mn, Re), 32,33 which can also be extended for [M(bpy)(CO) 3 ] -(M ) Mn, Re), have revealed that the electron density on the fivecoordinate metal center significantly increases in the order Re < Mn, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…32 On the other hand, the reason for the absence of the 2e catalytic route in the case of [Mn(bpy)(CO) 3 Cl] seems to be different. Recent studies of bonding properties of the anions [M(iPr-DAB)(CO) 3 ] -(M ) Mn, Re), 32,33 which can also be extended for [M(bpy)(CO) 3 ] -(M ) Mn, Re), have revealed that the electron density on the fivecoordinate metal center significantly increases in the order Re < Mn, i.e. upon proceeding from 5d to 3d transition metals, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, while the unsaturated radicals [Re(CO) 3 (α-diimine)]· form at room temperature fairly stable 18e paramagnetic species [Re(CO) 3 -(α-diimine)(Sv)]· (Sv = MeCN, PrCN), [56][57][58] analogous radicals were not observed for [Mn(CO) 3 (α-diimine)]·. [59] Redox Behaviour of [Os 2 Ru(CO) 10 …”
Section: Stability Of the Photoproductsmentioning
confidence: 99%